Processing TiC nanoparticle reinforced aluminum matrix composites in PBF-LB: Powder blending approach, particle sintering, precipitation and grain refinement - Raphael Freundl; Eric A. Jägle (Materials & Design)
Particle-reinforced aluminum-matrix-composites (AMCs) promise enhanced mechanical properties while maintaining the lightweight potential of aluminum. Fabricating AMCs near-net-shape is desirable because it avoids the drawback of the difficult machining. Laser powder bed fusion (PBF-LB) has the potential to achieve this goal. An economically attractive powder blending approach was used to modify AlSi7Mg0.6 powder with TiC nanoparticles. The resulting blend was processed in a PBF-LB machine to fabricate AMCs. This paper shows how to maximize the grain refinement potential of TiC nanoparticles by using a high mixing time of 1215 min to break up agglomerates. For a better understanding of the process related microstructure, investigations of the TiC distribution in blend and composites have been conducted by SEM and EDS. The formation of TiC microparticles formed by sintering of agglomerates are an integral part of the final microstructure. Measuring the overall carbon content of the specimens reveals a loss of TiC during PBF-LB. The root causes are discussed in terms of agglomeration and smoke generation and countermeasures are proposed. The presented approach is an effective way to introduce nanoparticles and to refine the microstructure. It can also be adapted to other material systems to modify the grain size and reduce the texture.